Effect of cultivar, proline acid and drought on some physiological characteristics of eggplant (Journal of the College of Basic Education, 2022)
I took the seeds of two cultivars of the banyan plant.] 712/01182714 Ha 5k and they are the cultivarThe first (Sun)] is an American variety of origin, and the second categoryIt is a Turkish variety. Three periods of thirst were used (0, 8, 16).A day and three concentrations of proline acid (0,50,100) were designed, respectivelyDilution law by three replications for each treatment. Seeds were planted in a nursery for one season2013, and the process of fertilization was carried out, and the plants were monitored daily, and after the plants arrivedThe stage of formation of 6-7 leaflets was exposed to the aforementioned treatments. Some characteristics were studiedPhysiology of the treated plant.